PSYCHOSOCIAL RISKS AT WORK: GENERAL CONCEPTS AND LEGAL FRAMEWORK IN ALGERIA - KIBBOUA , Mounia; KORICHI, Saïd (Journal of Human Sciences, 2022)
Work-related psychosocial risks known by the acronym "RPS" designate a particular category of occupational risks. These risks, which do not spare any sector of activity, can take several forms (such as stress, burn-out, violence at work, etc.). Just as the forms of these risks are varied; so are the factors. Indeed, the college of expertise on the statistical monitoring of psychosocial risks at work selected six categories in its final report. These risk factors can adversely affect the physical and mental health of employees, which requires regulation and adequate preventive measures. It is within this framework of ideas and to better understand these emerging risks in the world of work, this communication will first discuss some general notions in terms of RPS. Then, it will deal with the regulatory framework governing these risks in Algeria.